The productive university: an overview of the university’s relationship with society - Zerrougue, Mohamed Bachir (Journal of Human Sciences, 2021)
The University’s aims are to establish the foundation of global sustained development. The major role it plays within the societal network, makes it the cultural and scientifique attractor that enables members of the society, to deal with the difficulties encountered. As there are no space or time for solitary education within any given society, the real higher education is that which links persons and individuals lives with their society and its needs, so as to achieve sustained development. This is why succussful universities of our time are the ones that open their gates to the sosietal surrounding as a whole, and search to detect and cure evil and disease, it should work as an incubator as well asreflector to the aspiration of individuals in the society.